MODEL PENANAMAN NILAI KERJA (PNK) DI SMP - Muhammad Yahya (Jurnal Cakrawala Pendidikan, 2011)
Abstract: A Model for the Inculcation of Work Values in Junior High Schools. This research and development study aimed to produce a model for the Inculcation of Work Values (IWV) integrated in skills learning in junior high schools (JHSs). The development consisted of the stages of pre-development, development, and model application, involving 621 Years VIII and IX students of JHSs. The data were collected through observations and questionnaires, and analyzed using the descriptive technique and Structural Equation Modeling (SEM). The results were as follows. (1) The pre-development stage produced an IWV hypothetical model. (2) The dimensions of the IWV included work interest, work appreciation, technology mastery, entrepreneurship skill, and learning satisfaction. (3) The effective model for the IWV consisted of work motivation construction, production, advancement access, process, and clarification, work product meaning, exhibition and sale, and reflection, (4) The results of the SEM analysis showed that the model for the IWV was effective to develop work values among JHS students. Keywords: inculcation of work values (IWV), skill learning